Extremal Solutions and Relaxation Problems for Fractional Differential Inclusions - Juan J. Nieto; Abdelghani Ouahab; P. Prakash (Abstract and Applied Analysis)
We present the existence of extremal solution and relaxation problem for fractional differential inclusion with initial conditions.